RETRACTED: Awareness and infection prevention practices of hepatitis B virus among informal caregivers in public hospitals of Addis Ababa, Ethiopia, 2024 - Kasse, Tsehaynew; Solomon, Tebibu; Mesfin, Abel; Lonsako, Arega Abebe; Orkaido, Okaso; Agegnehu, Yalemzer; Haile, Addisalem (Frontiers in Epidemiology, 2024)
BackgroundHepatitis B virus (HBV) infection poses a significant global health challenge, leading to approximately 1.1 million deaths annually. Informal caregivers of HBV patients face an increased risk of exposure, yet there is limited research on their awareness and infection prevention practices. This study aimed to evaluate the awareness and practices regarding HBV among informal caregivers in public hospitals in Addis Ababa, Ethiopia, in 2024.MethodsAn institutional-based cross-sectional study was conducted from May 15 to July 15, 2024, involving 422 informal caregivers selected through a systematic random sampling. Data were collected using structured, interviewer-administered questionnaires that were pretested. The data were analyzed using SPSS version 26, with logistic regression identifying factors influencing awareness and practices, set at p < 0.05.ResultsOut of 414 surveyed caregivers (response rate: 98.1%), the mean age was 34.31 years (±12), with 63% female and 47.6% single. Only 24.9% (95% CI: 20.7–29.1%) showed good awareness, and merely 11.6% (95% CI: 8.5–14.7%) demonstrated good practices. Key factors associated with better awareness included caregivers' positive attitudes (AOR: 2.54) and patient functional levels (AOR: 1.9). Good practices were linked to higher education levels (AORs: 4.84 and 5.3), acute disease status (AOR: 3.6), and positive attitudes (AOR: 4.37).ConclusionsThe study reveals inadequate awareness and practices among informal caregivers compared to national averages. Awareness was linked to caregivers' attitudes and patient activity levels, while education, awareness, attitudes, and disease type significantly influenced good practices.